Language as an Identity Marker in Sumnima: A Socio-Linguistic Perspective - Sharma Kandel, Bhanu Bhakta (Journal of NELTA Gandaki, 2022)
BP Koirala’s novel Sumnima has a special use of language made as an identity marker between the characters of two major cultural groups: Brahmins and Kirats. The researchers have studied Sumnima from different other perspectives like Freudian psychoanalysis, humanism, nationalism and existentialism among others. However, the power of language used in it and the sociolinguistic influence created on human communities through the characters has been almost ignored. The main objective of studying the novel for this article is to find what effect has been created through language by the novelist in socio-cultural phenomenon and how language generates power and social status. The critical insights of socio-linguistics have been used to analyze the primary text. The researcher has found that the main function of language is not only as a means of communicating one’s ideas and feelings in day-to-day life but it has social, cultural and even psychological functions to perform. It is a very strong socio-cultural element that does not only guide the human society but also provides its users the whole array of knowledge and perception that function as one’s identity marker in the society. It has its effect on all human identity, knowledge and other aspects of life including human unconscious, culture, practices, social status, personal attainment and exercise of power. The way it creates and exercises power can be used as a teaching pedagogy as well.